Adherence to the World Cancer Research Fund/American Institute for Cancer Research recommendations and colorectal cancer risk. (November 2017) - Turati, Federica; Bravi, Francesca; Di Maso, Matteo; Bosetti, Cristina; Polesel, Jerry; Serraino, Diego; Dalmartello, Michela; Giacosa, Attilio; Montella, Maurizio; Tavani, Alessandra; Negri, Eva; La Vecchia, Carlo
Abstract: Background: The World Cancer Research Fund (WCRF) and the American Institute for Cancer Research (AICR) released in 2007 eight recommendations for cancer prevention on body fatness, diet and physical activity. Our aim is to evaluate the relation between adherence to these recommendations and colorectal cancer (CRC) risk. Methods: We pooled data from two Italian case–control studies including overall 2419 patients with CRC and 4723 controls. Adherence to the WCRF/AICR guidelines was summarised through a score incorporating seven of the WCRF/AICR recommendations, with higher scores indicating higher adherence to the guidelines. Odds ratios (ORs) of colorectal cancer were estimated using multiple logistic regression models. Results: Higher adherence to the WCRF/AICR recommendations was associated with a significantly reduced CRC risk (OR 0.67, 95% confidence interval, CI, 0.56–0.80 for a score ≥5 versus <3.5), with a significant trend of decreasing risk for increasing adherence (p < 0.001). Consistent results were found for colon (OR 0.67) and rectal cancer (OR 0.67). Inverse associations were observed with the diet-specific WCRF/AICR score (OR 0.71, 95% CI, 0.61–0.84 for ≥3.5 versus <2.5 points) and with specific recommendations on body fatness (OR 0.82, 95% CI, 0.70–0.97), physical activity (OR 0.86, 95% CI, 0.75–1.00), foods and drinks that promote weight gain (OR 0.70, 95% CI, 0.56–0.89), foods of plant origin (OR 0.56, 95% CI, 0.42–0.76), limiting alcohol (OR 0.87, 95% CI, 0.77–0.99) and salt intake (OR 0.63, 95% CI, 0.48–0.84). Conclusion: Our study indicated that adherence to the WCRF/AICR recommendations is inversely related to CRC risk. Highlights: A pooled analysis of 2 Italian studies with 2419 CRC cases and 4723 controls. The role of adherence to the WCRF/AICR guidelines on CRC was evaluated. Adherence to the guidelines was summarised through a score based on 7 recommendations. The WCRF/AICR score was significantly inversely related to CRC risk. Higher adherence to the WCRF/AICR guidelines was associated to a 30% reduced CRC risk.